Short-term effect of a developed warming moist chamber goggle for video display terminal-associated dry eye. - Ren, Yueping; Chen, Jie; Zheng, Qinxiang; Chen, Wei (BMC Ophthalmology, 2018)
Background: Video display terminal (VDT)-associated dry eye (DE) patients are the rising group worldwide, and moisture goggles are the preferable treatment since they are capable of improving tear film stability and DE discomfort. The current study aims to evaluate the short-term efficacy and safety of the developed warming moist chamber goggles (WMCGs) for VDT-associated DE patients.Methods: In this prospective self-control study, 22 DE patients (22 eyes) working with VDTs over 4 h daily were enrolled and instructed to wear WMCGs for 15 min. Sodium hyaluronate (SH, 0.1%) eyedrops were applied as a control on another day on these same patients, however 4 subjects denied the eyedrop application. The symptomatology visual analog scale (VAS) score, tear meniscus height (TMH), noninvasive tear film break-up time (NI-BUT), tear film lipid layer thickness (LLT), and bulbar conjunctival redness were assessed with Keratograph 5 M at baseline, 5, 30 and 60 min after treatment. The WMCGs wearing comfort was also evaluated.Results: The ocular discomfort evaluated by VAS decreased in the WMCGs group throughout 60 min (P<0.001), better than the control group levels (P ≤ 0.015). TMH, NI-BUT (including the first BUT and average BUT) increased than baseline level accross 60 min in the WMCG group (P ≤ 0.012), while those in the control group only showed temporary improvements in 5 min. LLT also increased obviously after WMCGs wear, while the change in the control group was nearly innoticeable. No adverse responses were detected.Conclusions: Temporary use of the WMCGs is able to relieve ocular discomfort, and improves tear film stability in DE patients for at least 1 h, making it a promising alternative to other treatments.